Raman microspectroscopy of individual algal cells: sensing unsaturation of storage lipids in vivo - Samek, Ota; Jonáš, Alexandr; Pilát, Zdeněk; Zemánek, Pavel; Nedbal, Ladislav; Tříska, Jan; Kotas, Petr; Trtílek, Martin (Sensors (Basel, Switzerland), 2010)
Algae are becoming a strategic source of fuels, food, feedstocks, and biologically active compounds. This potential has stimulated the development of innovative analytical methods focused on these microorganisms. Algal lipids are among the most promising potential products for fuels as well as for nutrition. The crucial parameter characterizing the algal lipids is the degree of unsaturation of the constituent fatty acids quantified by the iodine value. Here we demonstrate the capacity of the spatially resolved Raman microspectroscopy to determine the effective iodine value in lipid storage bodies of individual living algal cells. The Raman spectra were collected from three selected algal species immobilized in an agarose gel. Prior to immobilization, the algae were cultivated in the stationary phase inducing an overproduction of lipids. We employed the characteristic peaks in the Raman scattering spectra at 1,656 cm(-1) (cis C═C stretching mode) and 1,445 cm(-1) (CH(2) scissoring mode) as the markers defining the ratio of unsaturated-to-saturated carbon-carbon bonds of the fatty acids in the algal lipids. These spectral features were first quantified for pure fatty acids of known iodine value. The resultant calibration curve was then used to calculate the effective iodine value of storage lipids in the living algal cells from their Raman spectra. We demonstrated that the iodine value differs significantly for the three studied algal species. Our spectroscopic estimations of the iodine value were validated using GC-MS measurements and an excellent agreement was found for the Trachydiscus minutus species. A good agreement was also found with the earlier published data on Botryococcus braunii. Thus, we propose that Raman microspectroscopy can become technique of choice in the rapidly expanding field of algal biotechnology.
Keywords: tuky nenasycené; mikrořasy; Chlorophyta; algal cells; jod; Ramanova spektroskopie; analýza jednotlivých buněk; Single-Cell Analysis; Iodine; reprodukovatelnost výsledků; Biofuels; Fats, Unsaturated; lipids; plynová chromatografie s hmotnostně spektrometrickou detekcí; Raman spectroscopy; Reproducibility of Results; Spectrum Analysis, Raman; biopaliva; Gas Chromatography-Mass Spectrometry; Microalgae; iodine value